Design and Synthesis of C7-N-acetylneuraminic Acid Analogues as Potential Bacterial Sialic Acid Transport Inhibitors - Danko,Nadiia (2025)
Sialic acids or glyconic structures containing a sialic acid fragment are among the most abundant host surface molecules, typically found to be terminating branches of N-glycans, O-glycans, and glycosphingolipids (gangliosides). They play a crucial role in bacterial pathogenesis, due to the ability of bacteria to engage in molecular mimicry - the decoration of their surface with sialic acids - to avoid, subvert, or suppress the host's innate immunity. There are several ways to prevent this type of masking. One of them is to inhibit sialic acid uptake by bacteria using sialic acid transporter inhibitors. The design and synthesis of such inhibitors is the main idea of a large research project, of which this work is a part. Earlier, this research group has already carried out certain modifications of the main representative of this class, Neu5Ac, at the 4-OH, 5-NHAc and 9-OH positions, as well as 7-C, 8-C and the formation of 1,7-bicyclic lactam. Since the role of the glycol tail in the binding of this molecule to the protein pocket has not yet been fully investigated, it was decided to continue expanding the library of these compounds in the direction of modifying the 7-C position, starting with the corresponding aldehyde. Therefore, the aim of this project was to introduce an aromatic ring via bonding to the (S, O) heteroatom at the 7-C position of Neu5Ac and compare their properties.
Keywords: sialic acid; drug design; transport inhibitors; organic chemistry